2022
DOI: 10.4103/ua.ua_139_21
|View full text |Cite
|
Sign up to set email alerts
|

Role of inflammatory markers and their trends in predicting the outcome of medical expulsive therapy for distal ureteric calculus

Abstract: Objective: Symptomatic ureteric stones cause surrounding inflammation-promoting obstruction. C-reactive protein (CRP), white blood cell count (WC), and neutrophil percentage (NP) tend to rise after inflammatory response. Monitoring response during the course of medical expulsive therapy (MET) may help in deciding early intervention, thereby decreasing morbidity. We assessed the role and trends of these markers in predicting the outcome of MET. Materials and Methods: One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
3
5
0
Order By: Relevance
“…Across these studies, the majority of patients fell within the 20-45 age range. In multiple studies, age and sex did not show notable variances [27][28][29][30][31]. Furthermore, Ozcan et al [24] observed a higher rate of SSP in the younger age category, with no significant distinctions in sex between the groups, mirroring our findings.…”
Section: Discussionsupporting
confidence: 86%
“…Across these studies, the majority of patients fell within the 20-45 age range. In multiple studies, age and sex did not show notable variances [27][28][29][30][31]. Furthermore, Ozcan et al [24] observed a higher rate of SSP in the younger age category, with no significant distinctions in sex between the groups, mirroring our findings.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, neutrophil count only approached statistical significance (P = 0.06) in multivariable logistic regression but was observed to have a relevant impact on SSP through the modelling process. Previously Sfoungaristos et al [18] showed a significant association between neutrophilia and SSP which was not replicated in a more recent study [25]. Therefore, the exact predictive role of neutrophil count for SSP remains unclear.…”
Section: Discussionmentioning
confidence: 89%
“…Previously Sfoungaristos et al. [18] showed a significant association between neutrophilia and SSP which was not replicated in a more recent study [25]. Therefore, the exact predictive role of neutrophil count for SSP remains unclear.…”
Section: Discussionmentioning
confidence: 93%
“…Based on the stone location, the SSP will change ranging from 79%, 60%, and 48% for distal, mid, and proximal ureteral stones respectively. The EAU/AUA panel studied SSP based on a meta-analysis that showed 68% for <5 mm stones and 48% for 5–10 mm stones [ 24 ]. The current study showed a 55.9% SSP rate, and the stone size was significantly smaller in comparison with non SSP patients (6.43 ± 1.60 versus 7.76 ± 1.49) with a p-value < 0.001, while the rate of SSP concerning the stone location was 25%, 37,5%, and 61.2% for the proximal, mid and lower ureteral stones respectively which is relatively lower than the previously mentioned studies.…”
Section: Discussionmentioning
confidence: 99%